The Ottoman conquest of the Balkans : interpretations and research debates - Schmitt, Oliver Jens (Sitzungsberichte (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse), 2016)
The Ottoman conquest of the Balkans constitutes a major change in European history. Scholarship on the topic is extensive, yet the evidence produced by decades of research is very scattered and lacking comprehensive synthesis, not to mention consensual interpretation. Although major political and military milestones seem to have been investigated thoroughly, there is a notable absence of more theoretical and interpretative approaches that overarch the entire phenomenon rather than merely individual aspects. Scholars have hitherto addressed the topic from various perspectives and employing a wide range of methods, but Byzantine studies, Ottoman studies, Eastern Mediterranean studies and national historiographies in the Balkan countries have yet to establish either a coherent collaboration or a consistent model of interpretation. This volume therefore rather aims at opening and structuring a new heuristic approach and at coordinating a field of studies that is of crucial importance for understanding change in European history.